Violência sofrida e perpetrada: estudo epidemiológico com escolares da rede pública de ensino em Fortaleza-CE - Savioli, Kátia Costa (2015)
Violence involving the teenager is identified in its various expressions, remains a serious problem of public health and can make victims future aggressors, characterizing the complex cycle generated between suffering and perpetrating. The overall objective of the study was to analyze the epidemiology of violence suffered and perpetrated by adolescents from public schools in Fortaleza-CE. The method calls for an exploratory-descriptive study, cross-sectional analytical. The sample consisted of 360 adolescents (10-19 years) of both sexes enrolled in Municipal and State Schools. It was used to form the interviews and the data processed by the software STATA 13. The analysis was made through descriptive and inferential statistics. The chi-square test and Fisher exact tests were used to identify possible associations between covariates and outcomes suffered physical violence perpetrated during adolescence. It calculated the attributable risk proportion between the variables statistically significant (p <0.05). The negative binomial log regression was used to identify potential risk factors and their prevalence ratios (PR) adjusted to the outcomes. The criterion of AIC was used for decision the best model. Stratified analysis was made with the model variables and held comparing predictors by other methods (logistic regression, Poisson and Cox) in order to determine best measure of association to collate the risk in this type of study. The research answered the resolution 466/12 of the National Health Council and was approved by the Ethics Committee of the Federal University of Ceará- CEP / UFC. Among the findings were identified: 50.6% of adolescent females and 49.4% males, the average age amounted to 14.4 years and as the involvement with violence the study revealed high prevalence especially in the forms of psychological and physical expression, emphasizing at the stage of pre-adolescence, the school environment and peer relationship, revealing complex social reality and a pattern of action and reaction based on aggression and conflict resolution. The predictor variables that remained statistically significant in the model for physical violence suffered were having practiced physical violence (p <0.001); have suffered psychological violence (p <0.001); not attend family home in free time (p = 0.004); practice psychological violence (p = 0.015) and not participate in projects / social programs for professional qualification (p = 0.014). For the outcome perpetrated physical violence, were obtained: having suffered physical violence (p <0.001); We have already discontinued the study (p <0.001); perform in free time activities related to violence (p <0.001); being male (p = 0.005) and have had some kind of conflict with the law (p = 0.039). The issue announced reveals that family and school institutions deserve more space on the political agenda of public management, to build arguments and effective methods of promoting civility, culture of peace and healthy psychosocial development of this public display.